The Dark Side of Global Tourism: Unsustainable, Supercharged Commercialism, and Limited of the TBL (Third Sector Social Economic Review, 2025)
Climate change has been one of the most challenging and controversial topics in recent years despite the tons of studies, projects and developed sustainability criteria around the globe. A correlation exists between human activities and the decline in environmental quality as well as the depletion of renewable and finite resources. The growth of the tourism industry in global trade substantially elevates greenhouse gas emissions and underscores the pressing necessity for sustainable production and consumption practices. This observation necessitates a thorough analysis of the core motivations for production and consumption, encompassing human greed, ideological factors, and perspectives from sociology and philosophy. This study seeks to examine the interconnections among climate neutrality, sustainable production, and sustainable consumption using a critical conceptual approach. The investigation utilizes relevant papers and books assessed by critical evaluation techniques. Research reveals that sustainability efforts in the tourism industry frequently have a symbolic purpose, that Triple Bottom Line objectives (3P: People-Planet-Profit) encounter systemic limitations, and that insufficient understanding and irrational approaches and practices considerably impedes environmentally friendly production and use behaviors. The sustainability approach seeks to employ efficient methods to cultivate environmentally conscious choices in production and consumption, thereby mitigating the tourism industry's adverse effects on the environment. This study combines theoretical perspectives from social sciences to present a critical conceptual framework for sustainable tourism development by establishing a foundation for more comprehensive policy and practice recommendations.
Keywords: Global Tourism; Sustainbility; Sustainable Consumption; Sustainible Production; TBL